Study on the Correlation between Cervical Intraepithelial Lesions and Human Papillomavirus Infection and Vaginal Microecology - Qinghua Zhang; Yansong Liu; Changsheng Xu (Clinical and Experimental Obstetrics & Gynecology)
Background: The aim of this study was to explore the correlation between high-risk human papillomavirus (HR-HPV) infection and changes in vaginal microecology, as well as the severity of cervical intraepithelial lesions (CIN). Methods: A retrospective analysis was conducted on 221 inpatients (aged 23–80 years) who underwent simultaneous testing of vaginal secretions for microecological parameters, HR-HPV genotyping, and cervical tissue biopsy at the Department of Gynecology, Second Affiliated Hospital of Xinjiang Medical University, Urumqi, from October 2021 to January 2023. The study subjects were analyzed to determine the association between HR-HPV infection and alterations in vaginal microecology, as well as CIN. Results: Among the 221 cases, 69 were positive for HR-HPV, resulting in a positivity rate of 31.22% (69/221). Out of the 139 cases with normal vaginal microecology, 26 were positive for HR-HPV, yielding a positivity rate of 18.71% (26/139). Among the 82 cases with abnormal vaginal microecology, 43 were positive for HR-HPV, resulting in a positivity rate of 52.44% (43/82). Out of the 162 cases with normal cervix, 26 were positive for HR-HPV, resulting in a positivity rate of 16.00% (26/162). Among the 59 cases with abnormal cervix, 43 were positive for HR-HPV, resulting in a positivity rate of 72.88% (43/59). In the cases of abnormal cervix, 10 presented cervical inflammation, with a HR-HPV positivity rate of 70.00% (7/10); 20 cases had cervical intraepithelial lesions (CIN) I, with a HR-HPV positivity rate of 70.00% (14/20); 20 cases had CIN II, with a HR-HPV positivity rate of 75.00% (15/20); and 9 cases had CIN III, with a HR-HPV positivity rate of 77.80% (7/9). Moreover, among the 162 cases with normal cervix, 36 had abnormal vaginal microecology, resulting in an abnormality rate of 22.22% (36/162). Among the 59 cases with abnormal cervix, 46 had abnormal vaginal microecology, resulting in an abnormality rate of 77.97% (46/59). In the cases of abnormal cervix, 10 had cervical inflammation, with an abnormal vaginal microecology rate of 70.00% (7/10); 20 cases had CIN I, with an abnormal vaginal microecology rate of 70.00% (14/20); 20 cases had CIN II, with an abnormal vaginal microecology rate of 80.00% (16/20); and 9 cases had CIN III, with an abnormal vaginal microecology rate of 100.00% (9/9). The differences in HR-HPV positivity rates between the group with normal vaginal microecology and the group with abnormal vaginal microecology were statistically significant (p < 0.05). Similarly, the differences in HR-HPV positivity rates for different degrees of CIN were statistically significant (p < 0.05), as well as the differences in abnormal vaginal microecology rates for different degrees of CIN (p < 0.05). Conclusions: HR-HPV infection was found to be significantly associated with alterations in vaginal microecology and CIN.